Abortion outbreak caused by Campylobacter fetus subspecies venerealis and Neospora caninum in a bovine dairy herd - Macias Rioseco, Melissa; Caffarena, Rubén; Fraga, Martín; Silveira, Caroline; Giannitti, Federico; Canton, German Jose; Hecker, Yanina; Suanes, Alejandra; Riet Correa, Franklin (Instituto Nacional de Investigaciones Forestales, Agrícola y Pecuarias, México, 2020)
In November 2015, an abortion outbreak occurred in a commercial dairy herd of 650 Holstein cows in Florida department, Uruguay. Forty-five (45) cows aborted within 3 wk. Five fetuses were subjected to gross and microscopic pathologic examination, and microbiological testing. One fetus had fibrinous epicarditis and peritonitis, and neutrophilic bronchopneumonia. Campylobacter fetus subsp. venerealis was detected by direct immunofluorescence, isolated and identified by PCR and sequencing of the 16S rDNA in the abomasal fluid and/or lung. Histologic examination of two other fetuses revealed nonsuppurative necrotizing encephalitis, lymphohistiocytic myositis and myocarditis, and lymphocytic interstitial nephritis. In these fetuses, N. caninum antigen was detected intralesionally by immunohistochemistry, and N. caninum DNA was amplified by PCR on formalin-fixed paraffin-embedded brain. Antibodies against N. caninum were detected by indirect immunofluorescence in 10 of 27 cows, with titers ranging from 1/200 to 1/3200. The results indicate that two abortigenic microorganisms may coexist and cause contemporaneous abortion in a herd. It is relevant to highlight the importance of performing multiple diagnostic tests in various aborted dams and fetuses from the same herd for the etiologic confirmation of bovine abortion syndrome